Immunogenicity of an adjuvanted broadly active influenza vaccine in immunocompromised and diverse populations - Dylan A. Hendy; Erik S. Pena; Luis Ontiveros‐Padilla; Timothy A. Dixon; Denzel D. Middleton; Grace L. Williamson; Nicole Rose Lukesh; Sean R. Simpson; Rebeca T. Stiepel; Md Jahirul Islam; Michael A. Carlock; Ted M. Ross; et al. (Wiley, 2024)
Abstract Influenza virus outbreaks are a major burden worldwide each year. Current vaccination strategies are inadequate due to antigenic drift/shift of the virus and the elicitation of low immune responses. The use of computationally optimized broadly reactive antigen (COBRA) hemagglutinin (HA) immunogens subvert the constantly mutating viruses; however, they are poorly immunogenic on their own. To increase the immunogenicity of subunit vaccines such as this, adjuvants can be delivered with the vaccine. For example, agonists of the stimulator of interferon genes (STING) have proven efficacy as vaccine adjuvants. However, their use in high‐risk populations most vulnerable to influenza virus infection has not been closely examined. Here, we utilize a vaccine platform consisting of acetalated dextran microparticles loaded with COBRA HA and the STING agonist cyclic GMP‐AMP. We examine the immunogenicity of this platform in mouse models of obesity, aging, and chemotherapy‐induced immunosuppression. Further, we examine vaccine efficacy in collaborative cross mice, a genetically diverse population that mimics human genetic heterogeneity. Overall, this vaccine platform had variable efficacy in these populations supporting work to better tailor adjuvants to specific populations.